Can Natural Killer Cells Be a Principal Player in Anti-SARS-CoV-2 Immunity? - Ahmed, Faria; Jo, Dong-Hyeon; Lee, Seung-Hwan (Frontiers in Immunology, 2020)
The COVID-19 pandemic caused by SARS-CoV-2 virus infection is resulting in enormous loss of lives and devastating the global economy. Elderly populations and those with co-morbidities are often unable to clear the infection. With several hundred thousand people dead worldwide and many more infected, it is essential to understand the immunological response that results in beneficial or detrimental disease outcomes in this infection. Natural Killer (NK) cells from the innate immune system are early cytotoxic responders that can eradicate virus-infected cells and, therefore, may help control the infection. Besides, NK cells are not only responsible for target lysis but are also immunomodulators that produce pro-inflammatory or anti-inflammatory cytokines such as IFN-γ or IL-10, respectively. Notably, COVID-19 patients consistently experience a loss in total NK cell counts with increased expression of the NKG2A receptors, and such phenotypes are highly correlated to the severity of the disease. Several clinical trials have been initiated to perfuse NK cells to COVID-19 patients. Since numerous reports consistently indicate that COVID-19 patients develop a 'cytokine storm' with increased levels of multiple pro-inflammatory cytokines, trials employing NK cells holding the pro-inflammatory property would be not ideal. Here, we contemplate the impact of NK cell loss on NK cell immunity and cytokine storm in SARS-CoV-2 infection, and propose adequate NK cell therapies for COVID-19 patients.